2020
DOI: 10.1101/2020.07.09.20149955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Poorly Understood Disease? The Unequal Distribution of Excess Mortality Due to COVID-19 Across French Municipalities*

Abstract: While COVID-19 was already responsible for more than 500,000 deaths worldwide as of July 3, 2020, very little is known on the socio-economic heterogeneity of its impact on mortality. In this paper, we combine several administrative data sources to estimate the relationship between mortality due to COVID-19 and poverty at a very local level (i.e. the municipality level) in France, one of the most severely hit country in the world. We find strong evidence of an income gradient in the impact of the pandem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
4
12
1
Order By: Relevance
“…Likewise, it was also partly an effect of their economic precariousness since the OR of the working class decreased when it was adjusted for this variable. The latter result is consistent with economists’ work that has recently established that “the prevalence of the epidemic was higher in the poorer communes in France [ 21 ]. We also found that living in housing with less than one room per person tended to be linked to the risk of having been infected.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, it was also partly an effect of their economic precariousness since the OR of the working class decreased when it was adjusted for this variable. The latter result is consistent with economists’ work that has recently established that “the prevalence of the epidemic was higher in the poorer communes in France [ 21 ]. We also found that living in housing with less than one room per person tended to be linked to the risk of having been infected.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, our study did not exhibit any significant association between economic indicators and in-hospital COVID-19 incidence or mortality at the department level. This contrasts with a recently pre-published study that showed a larger impact of the pandemic on overall mortality in the poorest of the 35,000 French municipalities (62). The spatial scale of our analysis (department level) may have been too wide to identify such an association.…”
Section: Discussioncontrasting
confidence: 94%
“…Our results show that this overexposure during lockdown was partly a result of their health status (smoking and history of chronic disease and obesity). It was also partly an effect of their economic precariousness since the OR of the working class decreased when it was adjusted on this variable, a result consistent with economic work that has recently been established at a macroeconomic level in France 18 . We also found that living in housing with less than one room per person tended to be linked to the risk of having been contaminated.…”
Section: Discussionsupporting
confidence: 71%